Isolation and immunohistochemical characterization of periodontal ligament stem cells: A preliminary study - Bhavna Jha Kukreja; Kishore Gajanan Bhat; Pankaj Kukreja; Vijay Mahadev Kumber; Rajkumar Balakrishnan; Vivek Govila (Wolters Kluwer Medknow Publications, 2021)
Context: It is a known fact that periodontal tissue regeneration can be achieved by the use of periodontal ligament stem cells (PDLSCs). Current mainstay of periodontal treatment is focusing on stem cell tissue engineering as an effective therapy, making it important to isolate PDLSCs from periodontal tissues. Aims: The present research endeavor was undertaken to elucidate a technique for isolating PDLSCs for in vivo reconstructing the natural PDL tissue. Settings and Design: The study design involves In vitro prospective study. Materials and Methods: Premolar teeth were extracted from 12 patients who were under orthodontic treatment. PDL cells were scraped from their roots. Using 10 ml of Dulbecco's modified Eagle's medium with pH 7.2, the specimens of the periodontal tissue were transferred to laboratory where cell culture was done. Isolated stem cells were grown on 24-well microtiter plates-containing cover slips. They were incubated overnight at approximately 37°C in 95% air and 5% humidification. Anti-CD 45, CD73, CD90, CD105, and CD146 antibodies were used. After staining, cells were observed under phase-contrast microscopy and in inverted microscope. Results: The cells showed a marked growth and 90% confluence at day 6. Cells presented thin and long fibroblastic spindle morphology. Isolated PDLSCs showed colony-forming ability at the 14th day after seeding. Immunohistochemical staining of PDLSCs showed positive uptake for CD146, CD90, CD73, CD105, and negative uptake for CD45. Conclusions: The human PDLSCs can be clearly isolated and characterized by using CD90, CD73, CD146, and CD105 markers of stem cells.